2022
DOI: 10.21660/2022.98.1221
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Change of Mangrove Forest for Eco-Tourism in the South Coastal, Bangkalan, East Java-Indonesia

Abstract: The dynamic increase in human needs results in land changes in coastal areas, threatening the mangrove ecosystem's existence. The mangrove ecosystem in this area can be managed and developed as an ecotourism area to utilize and protect it. It is important to do this research to integrate mangrove forest management by assessing land change in other surrounding areas as a starting point for the study. This study aims to analyze changes in the use of mangrove land and surrounding land on the southern coast of Ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…All study locations that are currently mangrove tourism objects, such as Tajungan, Jung Koneng, and Labuhan Education Park, have the ideal mangrove thickness (width) for mangrove tourism objects. The thickness of the mangroves on the north coast of Bangkalan is greater than the thickness of mangroves on the south coast of Bangkalan, which ranges from 10-280 m (Wardhani et al 2022). It is also generally greater than the mangrove ecosystem at the Idaman Mangrove Ecotourism which mangroves thickness ranged from 127 to 209 m (Askar et al 2021), and in Nusa Penida Island, Bali which ranged from 200 to 500 m (Vipriyanti et al 2022).…”
Section: Mangrove Thicknessmentioning
confidence: 87%
See 2 more Smart Citations
“…All study locations that are currently mangrove tourism objects, such as Tajungan, Jung Koneng, and Labuhan Education Park, have the ideal mangrove thickness (width) for mangrove tourism objects. The thickness of the mangroves on the north coast of Bangkalan is greater than the thickness of mangroves on the south coast of Bangkalan, which ranges from 10-280 m (Wardhani et al 2022). It is also generally greater than the mangrove ecosystem at the Idaman Mangrove Ecotourism which mangroves thickness ranged from 127 to 209 m (Askar et al 2021), and in Nusa Penida Island, Bali which ranged from 200 to 500 m (Vipriyanti et al 2022).…”
Section: Mangrove Thicknessmentioning
confidence: 87%
“…The number of species found on the north coast of Bangkalan is more than in Rawa Timur mangrove forest that there are 14 species of mangrove derived from 10 genera of 8 families, on six PP's (1.50 ha) that have been established (Hidayat et al 2017); Mentawir Village, Penajam Paser District, East Kalimantan Province which found 12 species, with the R. apiculata was the dominant species (Kristiningrum et al 2019) namely R. apiculate, R. mucronata, and Avicennia sp. ; Jor Bay, East Lombok which is found seven mangrove species, namely A. marina, C. tagal, R. apiculata, R. stylosa, S. alba, S. caseolaris, and Lumnitzera racemosa (Zulhalifah et al 2021) and more than in the south coast of Bangkalan which is 7 species of A. marina, A. alba, B. gymnorhiza, R. apiculata, R. mucronata, R. stylosa, S. alba, and Nypa fruticans (Wardhani et al 2022). However, the number of mangrove species on the north coast of Bangkalan is still lower compared with the number of mangrove species found in the Mimika Region, Papua where 66 mangrove species consisting of 20 major, 10 minor, and 36 associate mangrove species were found (Setyadi et al 2021); and lower compared with Karimunjawa Island, Central Java with 24 species of mangrove (Rahmandhana et al 2022).…”
Section: Mangrove Species Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Image correction begins the analysis stage which consists of radiometric correction and geometric correction. The next stage is land use classification using Supervised Classification with the Maximum Likelihood algorithm [26].…”
Section: Land Use Analysismentioning
confidence: 99%
“…S. Kongdit and T. Ratanapongtra [33] found that Thailand is characterized by a wealth of natural resources suitable for ecotourism, which in turn can be combined with agritourism. The authors found that the Tourism Authority of Thailand has integrated agriculture together, which allows tourists to observe and see agricultural products and learn about the culture of people in the region.…”
mentioning
confidence: 99%